Exploring violence towards EMS personnel: a multiprofessional qualitative study - Riihimäki, Heikki; Peltonen, Laura-Maria; Lahti, Mari; Paulin, Jani (BioMed Central, 2026)
Background
Violence against emergency medical service personnel is common and often underreported, with verbal abuse being the most frequent form, but physical and sexual violence also occur. The consequences of such violence range from psychological distress to physical harm and organizational burden. Despite growing evidence of the phenomenon, the dynamic, situational and interactional nature of this violence as well as effective prevention strategies are still insufficiently understood. The objective of this study was to examine factors contributing to violence against EMS personnel before, during and after violent incidents.
Methods
This qualitative study employed two multiprofessional stakeholder workshops (n = 36) conducted in Finland in October 2024. Participants included professionals from the EMS setting and its related fields, as well as patient representatives. The workshops produced experiences and perspectives on violence against EMS personnel, focusing on incident dynamics of violent encounters. Data was analyzed using thematic analysis.
Results
Violence towards EMS personnel presents itself through three interrelated themes: the aggressor, the EMS personnel, and the organization and the EMS system. The findings indicate that these themes interact dynamically, with violent incidents shaped by individual behavior, professional practice and institutional conditions. Aggressor-related factors such as substance use, psychiatric illness, and altered mental states were described as increasing risk for violence. EMS personnel’s fatigue, inexperience, and moralizing attitudes were seen to increase vulnerability, whereas resilience and situational awareness were protective. At the organizational level, unclear risk-assessment protocols, inconsistent cooperation with the police, and limited post-incident support emerged as key challenges.
Conclusions
Violence against EMS presents itself as a multifactorial and dynamic phenomenon involving aggressor behavior, EMS personnel actions and organizational structures. Embedding de-escalation and disengagement competencies into training, strengthening system-level safeguards and implementing post-incident support are essential. The development of predictive models on how to manage risks at every stage of the EMS mission is warranted.